Balloon dilation of the eustachian tube: a tympanometric outcomes analysis. Issue 1 (December 2016) - Williams, Blair; Taylor, Benjamin; Clifton, Neil; Bance, Manohar
Abstract Background Eustachian tube dysfunction (ETD) is a common medical issue, occurring in at least 1 % of the adult population. Patients suffering from ET dysfunction typically present with complaints of hearing loss or sensation of pressure or plugged ear, which can lead to impaired quality of life. Over time ETD can result in conductive hearing loss or choleastatoma formation. Effective theraputic options for ET dysfunction are few. Eustachian tube balloon dilation is a novel surgical technique being used to treat ETD. The aim of our study is to objectively measure the success of Eustachian tube balloon dilation by comparing pre and post-operative middle ear pressures using tympanometric testing. Methods RA retrospective chart review was preformed on all patients who underwent balloon dilation of the Eustachian tube by authors NC or MB from 2010 to 2014. Pre and post-operative tympanograms were analyzed and categorized based on type (Type A, Type B, Type C). Success was defined by an improvement in tympanogram type: Type B or C to Type A, or Type B to type C. Pre and post-operative tympanograms were further analyzed using middle ear pressure values. Follow-up ranged from 3 to 15 months. Results Twenty-five ears (18 patients) were included in the study. Overall 36 % of ears had improvement in tympanogram type, and 32 % had normalization of tympanogram post-operatively. The Jerger tympanogram type improved significantly following the procedure (p  = 0.04). Patients also had statistically significant improvement in measured middle ear pressure post-operatively (P  = 0.003). Conclusion The natural history of Eustachian tube dysfunction is poorly understood, and evidence for current treatments are limited. Eustachian tube balloon dilation is a safe procedure, and produces significant improvement in tympanogram values up to 15 months post-operatively. Further refinement of patient selection and standardization of technique is required to optimize the effect of this therapy. Longterm follow-up data will clarify the persistence of the effect.